2009
DOI: 10.1016/j.tecto.2009.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Erosion-driven uplift of the modern Central Alps

Abstract: We present a compilation of data of modern tectono-geomorphic processes in the Central European Alps which suggest that observed rock uplift is a response to climate-driven denudation. This interpretation is predominantly based on the recent quantification of basinaveraged Late Holocene denudation rates that are so similar to the pattern and rates of rock uplift rates as determined by geodetic leveling. Furthermore, a GPS data-based synthesis of Adriatic microplate kinematics suggests that the Central Alps are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 114 publications
(150 reference statements)
6
99
0
Order By: Relevance
“…Wittmann et al (2007) measured Holocene erosion rates in Alpine river sediments, which correlate very well with geodetically based rock uplift rates. These relationships have been used to suggest that vertical movement of rock has mainly been caused by isostatic compensation of removed material (Champagnac et al, 2009). In thematically related studies, several authors concluded that erosion rates directly correlate with geomorphological variables like slope gradients and local-as well as basin-scale relief that can be extracted from digital elevation models (Granger et al, 1996;Schaller et al, 2001;Montgomery and Brandon, 2002).…”
Section: Motivation For This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Wittmann et al (2007) measured Holocene erosion rates in Alpine river sediments, which correlate very well with geodetically based rock uplift rates. These relationships have been used to suggest that vertical movement of rock has mainly been caused by isostatic compensation of removed material (Champagnac et al, 2009). In thematically related studies, several authors concluded that erosion rates directly correlate with geomorphological variables like slope gradients and local-as well as basin-scale relief that can be extracted from digital elevation models (Granger et al, 1996;Schaller et al, 2001;Montgomery and Brandon, 2002).…”
Section: Motivation For This Studymentioning
confidence: 99%
“…These high uplift rates were related to a combination of ongoing collisional processes (Persaud and Pfiffner, 2004), erosional (Champagnac et al, 2009) and glacial unloading (Gudmundsson, 1994). Uplift rates are highest in the eastern part of the study area (1.5 mm a −1 ) and decrease to < 0.3 mm a −1 towards Lake Geneva (Fig.…”
Section: Tectonicsmentioning
confidence: 99%
“…The European Alps are in a post-collisional regime (Champagnac et al 2009;Sue et al 2007;Nocquet 2012;Valla et al 2012), and are characterized by isostatic-related extension and uplift, due to the interaction between buoyancy forces and erosional dynamics (Sue et al 1999;Champagnac et al 2007;Sue et al 2007;Delacou et al 2008;Serpelloni et al 2013;Vernant et al 2013;Baran et al 2014). …”
Section: Recent Deformation In the Jura Mountainsmentioning
confidence: 99%
“…Most active mountain ranges have been extensively shaped throughout Quaternary glaciation, but have only remnants of glaciers and glacial landforms today. For that reason our understanding of coupling between glacial erosion and tectonic processes is mostly based on the study of the geomorphology of deglaciated landforms (Brocklehurst and Whipple, 2002Whipple, , 2007Champagnac et al, 2009), and on conceptual (Whipple et al, 1999), analytical (Tomkin and Roe, 2007), and numerical models (Tomkin and Braun, 2002;Tomkin, 2007;Herman and Braun, 2008;Yanites and Ehlers, 2012). The St. Elias Range provides the opportunity for direct field investigations of glacial erosion processes in an active orogen and testing glacial erosion models (e.g.…”
Section: Mountain Building and Erosionmentioning
confidence: 99%